Exigência de proteína digestível em dietas para juvenis de tambaqui e a dinâmica do crescimento muscular por aspectos morofológicos e turnover isotópico do carbono-13 e do nitrogênio-15 - Buzollo, Hellen [UNESP] (2014)
Among the native species with potential for aquaculture, tambaqui Colossoma macropomum is distinct for its hardness, ease of cultivation and adaptation to high productivity in intensive system. There is a lack of information about protein requirements for tambaqui. Thus, is it necessary to establish the requirements for this nutrient for better formulations of diets. An efficient use of protein allows the expression of better performance and optimum body characteristics. Efficient use of protein is also associated with less excretion of nutrients into the environment and cost reduction of feeding. The thesis is divided into four chapters, preseting an overview of the topics covered in the project and results are described in the form of articles for publication. Thus, we investigated, at first, the determination of apparent digestibility coefficients (ADC) of protein, ether extract and energy of the nine protein feedingstuffs (soybean meal, cottonseed meal, salmon meal, tilapia filleting residue meal, poultry by-product meal, feather meal, corn gluten, wheat gluten and alcohol yeast) and seven energy feedingstuffs (corn, sorghum, wheat meal, broken rice, soya oil, fish oil and corn oil), the most commonly used in commercial fish diets. The most of ADC protein feedingstuffs were high for the fractions of protein, ether extract and energy, with the exception of the ADC protein alcohol yeast, ADC ether extract to wheat gluten and ADC of energy for the cottonseed meal and alcohol yeast. All were less than 65%. Juvenile tambaquis availed well the energetic feeds, providing high ADC. Further, we determined the requirements of digestible protein for juvenile tambaquis, and to evaluate the mechanisms of hyperplastic and hypertrophic muscle growth. The protein level affected all parameters (P <0.005). The digestible protein requirement for tambaqui in our experimental conditions was 29%, causing changes in muscle cellularity, with increased ...